EVALUASI PRODUKTIVITAS ALAT GALI MUAT DAN ALAT ANGKUT UNTUK MATERIAL OVERBURDEN PADA PIT PE DI PT PRIAMANAYA ENERGI - Ridho Yovanda; Osi Kestri Hanumsi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to evaluate the productivity and work compatibility of loading and hauling equipment in overburden stripping activities at Pit PE of PT Priamanaya Energi, Lahat Regency, South Sumatra. The loading equipment used was a Komatsu PC 1250 excavator, while the hauling equipment consisted of Komatsu HD 785 dump trucks. The research method employed field surveys by collecting primary data in the form of cycle time for both loading and hauling equipment, supported by operational and field condition data. The analysis was conducted by calculating equipment productivity and match factor values. The results showed that the actual match factor was 0.78, indicating an imbalance in the working system and the presence of waiting time for the loading equipment. An evaluation was carried out by adding one hauling unit, resulting in an increased match factor of 0.98, which is close to the ideal condition. Factors affecting productivity include mining front conditions, haul road conditions, and loading patterns. Proper equipment matching can improve efficiency and productivity in overburden removal operations.Keywords: Productivity, Loading Equipment, Hauling Equipment, Match Factor, Overburden